Reconstruction Of Political Theory Of Islamic Law In The Context Of Legal Pluralism In Indonesia - Muthmainah , Muthmainah; Mutakin, Ali; Aziz, Abdul; Ngalim, Samingun; Samman, Siti Asiah (Yapilin Press, 2025)
This research is motivated by the dynamics of the relationship between Islamic law and national law in the context of legal pluralism in Indonesia. The plurality of legal systems that include customary law, Islamic law, and positive law poses conceptual and practical challenges in realizing substantive justice. The politics of Islamic law is often perceived as merely an attempt to formalize sharia, even though historically and theoretically it has great potential to become an ethical and moral instrument in the formation of national law. Therefore, this study aims to reconstruct the political theory of Islamic law in order to be able to adapt to the reality of legal pluralism without losing the values of maqāṣid al-syarī'ah. The research method used is a juridical-normative approach with descriptive qualitative analysis of primary and secondary legal sources, including laws and regulations, fiqh siyasah literature, and modern legal political theory. The analysis is carried out through historical, philosophical, and conceptual approaches to trace the evolution of political ideas of Islamic law in the context of modern statehood. The results of the study show that the political theory of Islamic law needs to be reconstructed from a formalist paradigm to a substantive paradigm by emphasizing the principles of benefit, social justice, and the protection of citizens' rights. This reconstruction places Islamic law not as an exclusive system, but as a source of inclusive and dialogical value in the national legal system. Thus, Islamic legal politics in Indonesia can play an active role in strengthening the ethics of legislation and constitutional moral consistency in the midst of legal pluralism